Efficacy of Microwave and Infrared Radiation in the Treatment of the Skin Lesions Caused by Leishmania major in an Animal Model - SE Eskandari; A Azimzadeh; M Bahar; Z Safai Naraghi; A Javadi; A Khamesipour; A Miramin Mohamadi (Tehran University of Medical Sciences, 2012)
Background: Cutaneous leishmaniasis caused by L. major is an important public health problem in endemic areas. The aim of this study was to explore the therapeutic effect of microwave and or infrared radiation in the treatment of lesion induced in BALB/c mice by L. major inoculation.Methods: The footpad lesion was induced in BALB/c mice by inoculation of L. major promastigotes subcutaneously. The lesion was treated with 600 watts power, 2.450 GHz frequency and/or infrared device with 150 watts and a wave length of 890 nanometres. The size of the lesion was recorded by footpad swelling measurement every 10 days. Results: The lesion growth was significantly hampered in treated mice compared with the untreated control group (P<0.05). Infrared radiation was more effective than microwave in inhibiting ulcer enlargement.Conclusion: Infrared radiation and microwave significantly hampered L. major lesion growth in BALB/c mice. This therapeutic effect was more in infrared radiation treated mice than microwave treated mice.